Fragmentos da educação indígena mẽhĩ (krahô): tecendo a vida cotidianamente - Melo, Felipe Kometani (2024)
This dissertation seeks to present fragments, written and visual, about Mẽhĩ (Krahô) Indigenous Education. Through my ethnographic experience, built over the ten years I lived among the mẽhĩ, i propose to narrate a learning trajectory, where both, the local regimes of production and circulation of knowledge and their (cosmo)politics of care and attention, as well as the “external” policies for indigenous people, including school education, audiovisual and socio-environmental strengthening projects carried out with indigenous associations. The concept of "indigenous education" is thought in this work as practices (pedagogies, strategies and policies) that, in addition to being the basis of mẽhĩ learning processes, open up perspectives for thinking about other ways of being, thinking and feeling the world. In this sense, based on the interest in the “ordinary” practices of community experience, my narrative aims to share everyday encounters and affections, creating conditions for us to be crossed and transformed, bringing correspondences and reactivating, even if in a smaller way, something that has been each increasingly devalued by dominant rationality, sometimes rendered incommunicable: the lived experience.